A randomised clinical trial to assess the effect of a dual treatment on myopia progression: The Cambridge Anti‐Myopia Study. (12th May 2013) - Allen, Peter M; Radhakrishnan, Hema; Price, Holly; Rae, Sheila; Theagarayan, Baskar; Calver, Richard I; Sailoganathan, Ananth; Latham, Keziah; O'Leary, Daniel J
Abstract Purpose To evaluate the effect of a dual treatment modality for myopia, by improving accommodative functions, on myopia progression. Methods A double blind randomised control trial was conducted on 96 subjects. The treatment modality for the trial employed custom designed contact lenses which control spherical aberration in an attempt to optimise static accommodation responses during near‐work, and a vision‐training programme to improve accommodation dynamics. Myopia progression was assessed over a 2 year period using cycloplegic autorefraction and biometry. Results The mean progression was found to be −0.33 Dioptres (D) over the 2 years of the study. There was no interaction between contact lens treatment and vision training treatment at 24 months (p = 0.72). There was no significant treatment effect of either Vision Training or Contact Lens Spherical Aberration control on myopia progression. Conclusions This study is unable to demonstrate that the progression of myopia can be reduced over a 2 year period by either of the two treatments aimed at improving accommodative function. Neither treatment group (contact lens or vision training) progressed at a slower rate over the 2 years of the study than did the appropriate control group.